An Ergonomic Evaluation Of Excavating Operations: A Pilot Study - N. Kumar Kittusamy; Bryan Buchholz (The National Institute for Occupational Safety and Health (NIOSH))
Previous studies indicate that operators of heavy construction equipment are afflicted by musculoskeletal injuries of the arms, shoulders, neck, and lower back. These injuries appear to be due to excessive periods of sitting (static posture), work intensity, whole-body vibration, high resistance levers, repetitive motions, and awkward postures. (2-5) Although numerous studies have shown an association between operation of heavy construction equipment and symptoms of musculoskeletal disorders, very little research has been performed that systematically characterizes operating engineers' exposure to ergonomic hazards. The objective of this study was to systematically characterize the ergonomic hazards associated with excavating operations. As such, the following were performed: (1) vibrations were measured at the operator/seat interface (X, Y, and Z axes), and at the floor of the cab (Z axis); (2) psychophysical ratings of whole-body vibration (WBV) level and overall seat design were obtained; and (3) postural assessments of the job were made. Methodology This study evaluated an inexperienced female operator performing excavation, utilizing two different pieces of equipment. The operator was 37 years old, 162 cm tall, and weighed 80 kg. She had approximately 15 hours of operation time (experience) on the equipment evaluated. The two pieces of equipment used were: a Case Super 580E (1986) backhoe/loader, and an Insley H-2000 excavator (1975) (see Figures 1 and 2). More evaluations were performed on the backhoe/loader than on the excavator. The following evaluations were performed on the Case equipment: 1) vibration levels at the seat and floor; 2) psychophysical ratings of the overall seat design and vibration levels (for the task duration, and for an 8 hour duration); and 3) postural assessments. For the Insley equipment, all of the evaluations were performed except vibration measurements. When the evaluations were conducted, the following environmental conditions were noted: the temperature was 31°F, and soil and terrain conditions were rough and frozen.